Rozwiązywanie konfliktów interpersonalnych. O potrzebie uzupełnienia ujęcia psychologicznego o refleksję filozoficzną - Rumianowska, Agnieszka (Studia Edukacyjne, 2022)
Analysing contemporary works on patterns of interpersonal conflict formation and resolution, one can quite easily notice the predominant tendency to reduce the problem of interpersonal disputes exclusively to psychological and pedagogical issues. Thus, matters such as the root causes of conflicts, attitudes towards them and conflict resolution strategies predominate. Conclusions arising from the research are reflected in recommendations and proposals with regard to conflict resolution in the school, work or family environment. Not denying in any way the importance of the research results on the psychological determinants of problematic interpersonal relations and the resulting recommendations, it is worth asking whether psychological knowledge, awareness of one’s own needs, communication and negotiation skills are sufficient to effectively confront difficulties in interpersonal relations and fulfil oneself as a person. This article attempts to argue for the inclusion of philosophical issues in the discussion of interpersonal conflict resolution, with a special focus on issues derived from existential philosophy of a theistic nature and personalism.